Signaling by Drosophila capa neuropeptides. - Davies, S.A.; Cabrero, P.; Povsic, M.; Johnston, N.R.; Terhzaz, S.; Dow, J.A. (General and Comparative Endocrinology, 2013)
The capa peptide family, originally identified in the tobacco hawk moth, Manduca sexta, is now known to be present in many insect families, with increasing publications on capa neuropeptides each year. The physiological actions of capa peptides vary depending on the insect species but capa peptides have key myomodulatory and osmoregulatory functions, depending on insect lifestyle, and life stage. Capa peptide signaling is thus critical for fluid homeostasis and survival, making study of this neuropeptide family attractive for novel routes for insect control. In Dipteran species, including the genetically tractable Drosophila melanogaster, capa peptide action is diuretic; via elevation of nitric oxide, cGMP and calcium in the principal cells of the Malpighian tubules. The identification of the capa receptor (capaR) in several insect species has shown this to be a canonical GPCR. In D. melanogaster, ligand-activated capaR activity occurs in a dose-dependent manner between 10(-6) and 10(-12)M. Lower concentrations of capa peptide do not activate capaR, either in adult or larval Malpighian tubules. Use of transgenic flies in which capaR is knocked-down in only Malpighian tubule principal cells demonstrates that capaR modulates tubule fluid secretion rates and in doing so, sets the organismal response to desiccation. Thus, capa regulates a desiccation-responsive pathway in D. melanogaster, linking its role in osmoregulation and fluid homeostasis to environmental response and survival. The conservation of capa action between some Dipteran species suggests that capa's role in desiccation tolerance may not be confined to D. melanogaster.